PERANAN SELF-EFFICACY TERHADAP KETERLIBATAN KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI MEDIATOR PADA KARYAWAN GEN Z DI COFFEE SHOP KOTA PONTIANAK - Sari, Agnes Sima Angelina; Octora, Sandra Endang Suci (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to examine and evaluate the influence of self-efficacy on the engagement of Gen Z employees in coffee shops in Pontianak City, with work motivation as a mediating variable. The study applies a quantitative approach and purposive sampling technique for sampling. A total of 150 Gen Z employees, aged 18-28 years, working in coffee shops in Pontianak City, will be the respondents. Questionnaires were used to gather data and Structural Equation Modeling based Partial Least Squares (SEM-PLS) was used for analysis with the help of the WarpPLS 8.0 testing tool. The findings revealed showed that self-efficacy has a positive and significant influence on both employee engagement and work motivation. Work motivation has a positive and significant influence on employee engagement. Additionally, work motivation is able to significantly mediate the correlation between self-efficacy and employee engagement.